After Cognitivism A Reassessment of Cognitive Science and Philosophy - Leidlmair, Karl. (Springer Netherlands, 2009)
The present book comprises a collection of papers dealing with the reassessment of thinking in Cognitive Science and in Philosophy today. Still dependent on basic assumptions of Cartesian philosophy, Cognitive Science took over the mistakes of classical computational models. Instead of being treated as mere or pure explanations of mental processes with hindsight, these models were mistakenly used as more or less literal causal descriptions of the (working of the) mind. A clear insight into the relevance of embodied and embedded knowledge is not only a central topic in AI research; it can become a driving force for a reassessment of philosophy. Philosophy, which is struggling with the two opposite alternatives of cultural relativism and rationalism, both of which have turned out to be dead ends, is in need of a reassessment of reasoning. What is needed is a reasoning without reference to ultimate reasons which at the same time is grounded (and doesnt fall into the trap of cultural relativism).